Self-Regulation and Obedience of New Students in College Transition: Pengaturan Diri dan Ketaatan Mahasiswa Baru dalam Transisi ke Perguruan Tinggi - Sontani, Sonya Kusnanda; Maryam, Effy (Universitas Muhammadiyah Sidoarjo, 2025)
Background: University students often struggle to adapt to new academic and social demands, affecting their compliance with institutional rules. Specific Background: Previous research has examined self-regulation in relation to academic achievement, but few studies focus on compliance behavior in higher education. Gap: Limited research explores the relationship between self-regulation and compliance among Indonesian university students. Aim: This study analyzes the relationship between self-regulation and compliance at Muhammadiyah Sidoarjo University. Method: Using a quantitative correlational design, 320 students were selected through accidental sampling. Data were collected using reliable Likert-scale instruments and analyzed with Spearman Rho correlation in SPSS 26. Results: A strong positive correlation was found (r = 0.930, p < 0.05), indicating that higher self-regulation leads to higher compliance. Novelty: This study focuses on student compliance in the Indonesian higher education context with a robust statistical approach. Implications: Findings suggest that universities should implement self-regulation development programs to foster responsible and compliant student behavior. Highlights:• Strong positive relationship between self-regulation and compliance• Majority of students have moderate self-regulation and compliance levels• Implications for university policies and student development programs Keyword: Self-Regulation, Compliance, University Students, Academic Behavior, Higher Education